Challenges and Opportunities in the Implementation of Sharia Management - Aravik, Havis; Amri, Hoirul; Hamzani, Achmad Irwan; Khasanah, Nur (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
This research aims to explore the challenges, opportunities, and strategies in the implementation of sharia management in the era of globalization. In the context of modern business that is increasingly competitive, sharia management is faced with various challenges, including a lack of understanding of sharia principles, differences in regulations in different countries, and challenges in public education. Meanwhile, opportunities for the development of sharia management are increasingly open with the rapid growth of the halal industry and the increasing demand for products that are in accordance with ethical and sustainability principles. Through a literature approach, this study analyzes various literature to identify existing challenges, explore potential that can be utilized, and formulate effective strategies to overcome these obstacles. The findings of the study show that increasing sharia literacy, the adoption of information technology, and collaboration between the public and private sectors are strategic steps that can help sharia management compete in the global market. This research is expected to contribute to the development of sharia management as well as practical recommendations for industry players and policymakers in facing modern business dynamics